2014
DOI: 10.1021/ja5107404
|View full text |Cite
|
Sign up to set email alerts
|

2,2,2-Trichloroethyl Aryldiazoacetates as Robust Reagents for the Enantioselective C–H Functionalization of Methyl Ethers

Abstract: A new class of reagents is described for C-H functionalization by means of C-H insertion using donor/acceptor-substituted rhodium(II) carbene intermediates. The 2,2,2-trichloroethyl aryl and heteroaryl diazoacetates, together with the dirhodium triarylcyclopropane carboxylate catalyst Rh2(R-BPCP)4, enabled the enantioselective intermolecular C-H functionalization of a range of methyl ethers with high levels of site selectivity and enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 33 publications
1
73
0
Order By: Relevance
“…31-33 The TCE aryldiazoacetates have been reported recently as robust reagents and were successfully applied to the selective asymmetric C–H functionalization of methyl ethers by the Davies group. 26 Furthermore, the TCE group can be used with heteroaryldiazoacetates generating heteroaryl-substituted cyclopropanes, further expanding the scope of the reaction. Like TMSE, the TCE ester can be cleaved under mild conditions with Zn/AcOH (see supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31-33 The TCE aryldiazoacetates have been reported recently as robust reagents and were successfully applied to the selective asymmetric C–H functionalization of methyl ethers by the Davies group. 26 Furthermore, the TCE group can be used with heteroaryldiazoacetates generating heteroaryl-substituted cyclopropanes, further expanding the scope of the reaction. Like TMSE, the TCE ester can be cleaved under mild conditions with Zn/AcOH (see supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…25 Furthermore, in combination with the more sterically hindered 2,2,2-trichloroethyl aryldiazoacetates, site selective and enantioselective C–H functionalization of methyl ethers was achieved. 26 …”
Section: Introduction1mentioning
confidence: 99%
“…Use of a Troc ester in 2j required no slow addition, giving excellent dr in 3aj . 14 The [3+1] reaction was also successful when the aryl of the diazo compound was replaced with a Me in 2ak . Dimerization of the diazoacetate was solved using multiple equivalents of 2k to provide 3ak in good dr .…”
mentioning
confidence: 99%
“…As the vinylogous reaction would be expected to generate zwitterionic intermediates, we decided to use electron rich 2‐siloxydienes as trapping agents. We have recently found that carbenes substituted with trichloroethyl esters often give a much cleaner reaction than the traditional methyl ester derivatives, and so, we chose the vinyldiazoacetate 21 as the initial carbene precursor. The study was conducted with two catalysts, Du Bois’ Rh 2 (esp) 2 , which is a relatively bulky achiral catalyst and the chiral catalyst Rh 2 ( R ‐ p ‐PhTPCP) 4 , which is one of our recently reported extremely bulky chiral catalysts .…”
Section: Methodsmentioning
confidence: 99%
“…We have recently found that carbenes substituted with trichloroethyl esters often give a much cleaner reaction than the traditional methyl ester derivatives, and so, we chose the vinyldiazoacetate 21 as the initial carbene precursor. The study was conducted with two catalysts, Du Bois’ Rh 2 (esp) 2 , which is a relatively bulky achiral catalyst and the chiral catalyst Rh 2 ( R ‐ p ‐PhTPCP) 4 , which is one of our recently reported extremely bulky chiral catalysts . The reaction of the vinyldiazoacetate 21 with the first diene examined, 2‐siloxybutadiene 20 , gave the [4+3] cycloadduct 22 with both catalysts.…”
Section: Methodsmentioning
confidence: 99%